Phytopathogenic fungus hosts a plant virus: A naturally occurring cross-kingdom viral infection - Andika, Ida Bagus; Wei, Shuang; Cao, Chunmei; Salaipeth, Lakha; Kondo, Hideki; Sun, Liying (Proceedings of the National Academy of Sciences - PNAS, 2017)
The transmission of viral infections between plant and fungal hosts has been suspected to occur, based on phylogenetic and other findings, but has not been directly observed in nature. Here, we report the discovery of a natural infection of the phytopathogenic fungus by a plant virus, cucumber mosaic virus (CMV). The CMV-infected strain was obtained from a potato plant growing in Inner Mongolia Province of China, and CMV infection was stable when this fungal strain was cultured in the laboratory. CMV was horizontally transmitted through hyphal anastomosis but not vertically through basidiospores. By inoculation via protoplast transfection with virions, a reference isolate of CMV replicated in and another phytopathogenic fungus, suggesting that some fungi can serve as alternative hosts to CMV. Importantly, in fungal inoculation experiments under laboratory conditions, could acquire CMV from an infected plant, as well as transmit the virus to an uninfected plant. This study presents evidence of the transfer of a virus between plant and fungus, and it further expands our understanding of plant-fungus interactions and the spread of plant viruses.